Rasionalisasi Pola Penggunaan Anti Biotik Pada Pasien Balita Penyakit Demam Dan Batuk Rawat Jalan Di RSUD Tuan Rondahaim Pematang Raya Kabupaten Simalungun Periode Januari – Maret - I Ngurah Gede Verar Fujastawan; Bernido Raflo Purba; Marthalena Erbin Nahak; Dilla Sastia Mara; Muharti Sanjaya (Jurnal Kesehatan, 2021)
Antibiotic drugs are intended to prevent and treat infectious diseases. Recently, however, experts and doctors have found that antibiotics are not as effective as they used to be. The frequency of using antibiotics that is high but not matched by appropriate or irrational provisions can have negative impacts, one of which can be resistance. This study aims to determine the rationalization of the pattern of antibiotic use in under-five patients at Tuan Rondahaim Hospital Pematang Raya, Simalungun Regency for the period January-March 2018 through retrospective data collection by means of secondary data collection. The research sample was 275 toddler patients. The results showed that the use of the most antibiotics was amoxicillin by 47.63%, the dose of antibiotics that fulfilled the rational category was 100%, and the irrational category was 0%. Antibiotic indications that show 100% rational categories, 0% irrational categories, length of use of antibiotics that meet 100% rational categories, 0% irrational categories.